2016
DOI: 10.1016/j.ijms.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Direct Mass Spectrometric Analysis of Zinc and Cadmium in Water by Microwave Plasma Torch Coupled with a Linear Ion Trap Mass Spectrometer

Abstract: Microwave plasma torch (MPT) is a simple and low power-consumption ambient ion source. When MPT Mass spectrometry is applied in the detection of some metal elements, the metallic ions exhibit some novel features which are different with traditional ICP Mass spectrometry and may be helpful for the metal element analysis. Zinc and cadmium both are important transition metals with wide applications in modern industry. Here, we presented the research results about the MPT mass spectra of zinc and cadmium elements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Moreover, these methods have been a breakthrough in the application of MS to high‐throughput analyses where the samples are placed directly between the ambient environment and the vacuum inside the mass spectrometer so that the state of the sample can be ignored . Depending on the ionization/post‐ionization methods, ambient techniques can be divided into the following three classes: (1) interaction with spray‐droplets, including desorption electrospray ionization (DESI) and probe electrospray ionization (PESI); (2) multimodal ionization containing both electrospray and plasma (where the interaction with the plasma stream is generated by an electric discharge), including direct analysis in real time (DART), microwave plasma torch (MPT), and low temperature plasma (LTP) analysis methods; and (3) ionization/desorption with radiation, including laser desorption electrospray ionization (LDESI) . These ambient ionization sources have been used to analyze a wide variety of compounds, ranging from small molecules to biomacromolecules, including nondestructive, high‐throughput, and reaction‐monitoring analyses .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these methods have been a breakthrough in the application of MS to high‐throughput analyses where the samples are placed directly between the ambient environment and the vacuum inside the mass spectrometer so that the state of the sample can be ignored . Depending on the ionization/post‐ionization methods, ambient techniques can be divided into the following three classes: (1) interaction with spray‐droplets, including desorption electrospray ionization (DESI) and probe electrospray ionization (PESI); (2) multimodal ionization containing both electrospray and plasma (where the interaction with the plasma stream is generated by an electric discharge), including direct analysis in real time (DART), microwave plasma torch (MPT), and low temperature plasma (LTP) analysis methods; and (3) ionization/desorption with radiation, including laser desorption electrospray ionization (LDESI) . These ambient ionization sources have been used to analyze a wide variety of compounds, ranging from small molecules to biomacromolecules, including nondestructive, high‐throughput, and reaction‐monitoring analyses .…”
Section: Introductionmentioning
confidence: 99%
“…As a novel high‐frequency plasma generator at atmosphere pressure, the MPT ionization source was developed in 1985 at Jilin University of China, and substantial improvements were subsequently made at Indiana University . The traditional applications of the MPT were mainly focused on optical spectroscopy in the excitation source to analyze metallic and nonmetallic elements . Recently, the MPT has begun to be used as an ion source for ambient mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%
“…ICP-MS is a quite sensitive elemental analysis method and can determine the contents of titanium and zirconium. Nevertheless, in the current field analytical sense, ICP-MS is limited due to the general essential tedious chemical pretreatment, expensive and cumbersome equipment [ 17 , 18 , 19 ]. Microwave plasma torch (MPT)-mass spectrometry is one of the recently developed ambient mass spectrometric techniques with numerous merits.…”
Section: Introductionmentioning
confidence: 99%
“…The plasma technique possesses strong excitation ability and good universality, hence MPT has been used widely as a powerful light source in spectrometric instruments [ 21 , 22 , 23 , 24 , 25 , 26 ], and even then been applied in the direct analysis of solid samples [ 27 ]. Our previous studies have showed that the MPT, as an ambient ion source, coupled with a linear ion trap mass spectrometer, can be a potential analytical tool in various fields, especially in the analysis of metal elements [ 17 , 18 , 19 , 20 , 28 ]. By adopting a desolvation unit, and injecting aqueous samples through the central-tube of the MPT unit, MPT-mass spectrometry has been applied to detect directly and sensitively many kinds of metal elements in water without tedious sample pretreatment procedures [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation